How Software Development Methodologies Affect Dynamic Capabilities Under Extreme Contexts: A COVID-19 Study on Agile and Waterfall Methodologies - Salnikov, Nikita (2021)
Software development methodologies affect different aspects of software as a service companies. This research studies a particular effect – how a software development methodology affects dynamic capabilities of a company. Another aspect that this research studies is whether these effects would be different under different contexts – normal and extreme contexts. In this research, a real-life case company is studied, which survived through the COVID-19 pandemic. It is analysed how the software development methodology helped and evolved, and how the effects of the methodology on dynamic capabilities changed.